The role of radiotherapy in elderly women with early-stage breast cancer treated with breast conserving surgery. Issue 6 (December 2018) - Valli, Mariacarla; Cima, Simona; Fanti, Paola; Muoio, Barbara; Vanetti, Alessandra; Azinwi, Che N.; Yordanov, Kaloyan; Martucci, Francesco; Pesce, Gianfranco A.; Canonica, Claudia; Richetti, Antonella
Objective: To analyze the impact of adjuvant radiotherapy (RT) on ipsilateral breast recurrence (IBR) and overall survival (OS) in patients older than 69 years with early-stage breast cancer. Methods: From January 2007 to June 2015, we analyzed retrospectively 137 women with estrogen receptor–positive T1–2 invasive breast cancer, with negative axillary lymph nodes, dividing them into 2 subgroups: 70 to 79 years and older than 79 years. Results: After a median follow-up of 43.2 months, the 3-year IBR-free survival in patients treated with surgery plus RT was 98.8% and 92.1% in patients treated with surgery alone, with a significant difference ( p = .01). Radiotherapy did not impact overall survival ( p = .10). A higher percentage of patients aged between 70 and 79 years received RT after conservative surgery if compared with the older subgroup ( p < .01). Conclusions: In elderly women, adjuvant RT reduced the IBR, but did not improve OS.